1998
DOI: 10.1161/01.atv.18.11.1679
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated Fatty Acids Increase Plasminogen Activator Inhibitor-1 Expression in Endothelial Cells

Abstract: Abstract-In vivo studies have demonstrated a strong positive correlation between plasma very low density lipoprotein (VLDL) triglyceride and plasma plasminogen activator inhibitor-1 (PAI-1) activity levels. Furthermore, VLDL has been shown to induce PAI-1 secretion from cultured endothelial cells. In contrast, no or variable effects on PAI-1 secretion have been reported for native low density lipoprotein. It could be speculated that fatty acids derived from VLDL triglycerides are the actual mediators, resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 51 publications
5
48
1
1
Order By: Relevance
“…Non-esterified fatty acids also suppress nitric oxide production in vitro [35] and this could increase blood pressure [36]. The production of PAI-1 is induced by NEFA, a process which possibly involves induction of gene transcription by intracellular fatty acids [37].…”
Section: Discussionmentioning
confidence: 99%
“…Non-esterified fatty acids also suppress nitric oxide production in vitro [35] and this could increase blood pressure [36]. The production of PAI-1 is induced by NEFA, a process which possibly involves induction of gene transcription by intracellular fatty acids [37].…”
Section: Discussionmentioning
confidence: 99%
“…The fibrates decrease PAI-1 production stimulated by insulin in hepatocytes in vitro. (Alessi & Juhan-Vague, 2006;Alessi et al, 2007;Asplund-Carlson et al, 1993;Eriksson et al, 1998;Li et al, 1997;Nilsson et al, 1998;Schneider & Sobel, 1996;Stiko-Rahm et al, 1990). …”
Section: Free Fat Acids and Lipoproteins With Very Low Densitymentioning
confidence: 99%
“…5,6 NEFAs have been shown to induce both hepatic and peripheral IR, 7,8 to activate apoptotic pathways in pancreatic b cells, 9 to promote endothelial dysfunction 10 and to increase the production of plasminogen activator inhibitor-1. 11 Most importantly, increased NEFA supply of the liver, primarily owing to the incomplete insulin-mediated suppression of lipolysis in this type of subjects, is the initial step for the development of the characteristic lipid disorders of the metabolic syndrome. 12 With regard to hypertension, several studies have clearly shown a causal association of IR and compensatory hyperinsulinaemia with blood pressure (BP) elevation, through mechanisms like sodium retention, stimulation of the sympathetic nervous system, promotion of vascular cell's growth or impairment of insulin-mediated vasodilatation in insulin-resistant states.…”
Section: Introductionmentioning
confidence: 99%